2015 INDUCTION OF ASSBI FELLOWS. Issue 3 (26th January 2016) - Unknown
Abstract : Glynda joined ASSBI in 1980 was on the Executive Committee as President Elect in 2007 and became the President in 2009–2011. She has made a significant and long standing contribution to ASSBI and has also made a distinguished contribution to research in the field of TBI and disorders of ageing, and as an educator of Clinical Neuropsychology.